PERANCANGAN SISTEM INFORMASI RUMAH KOST BERBASIS WEB - Herison Halim; Dedi Trisnawarman; Desi Arisandi (Fakultas Teknologi Informasi Universitas Tarumanagara, 2016)
Boarding house is a place that is leased to another people by providing facilities with a cheaper price than stay at the hotel. The purpose of designing this information system is to help peoples looking for a boarding house and to help peoples to booked a boarding room. The method used in the design boarding house information system are using SDLC (System Development Life Cycle). System Development Life Cycle methods have four stages, planning phase, analysis phases, design phases, and the implementation phase. The web development using PHP and MYSql application as databases. Testing website design using blackbox testing namely the owner of the boarding house and people using the website programs and give a feedback to develop the website. Testing was conducted by two users, namely, the owner of the boarding house part and user member. The results of the test by the owner of the boarding house is payment checks from the web very easy. Because the web admin will send proof of payment to email. The results of the tests performed by the user member, namely in the boarding room reservation is very easy.